Extramedullary Hematopoiesis Involving the Bilateral Lacrimal Fossae - Baskurt, E.; Raghavan, P.; Trelka, D.P. (American Journal of Neuroradiology, 2006)
SUMMARY: Extramedullary hematopoiesis is a complication of a number of myeloproliferative disorders. MR imaging of the orbits was performed in a patient with bilateral orbital swelling with known myeloproliferative disorder and myelofibrosis. The study revealed symmetric, bilateral enhancing masses in the lacrimal fossae extending into the nasolacrimal ducts. Biopsy demonstrated sclerotic extramedullary hematopoietic tumor.